Sewer, gas & electric : the public works trilogy : a novel - Ruff, Matt (Grove Press, 1997)
A computer-generated plague sweeps the world, killing every black person in sight. This is one of a number of doomsday events contained in this futuristic novel where mayhem follows mayhem. In another, a shark is creating havoc in New York's sewer system.